Blood Pressure Levels among the Students of a Selected School (Ibrahim Medical College Journal, 2010)
In Bangladesh, limited data are available on paediatric hypertension as well as their normal values.This study was done to assess the level of blood pressure in this population group. A total of 1118students from class I to X of a selected school were measured twice for systolic and diastolic BPwithin five minutes interval following a standard protocol. The phase V diastolic blood pressure wasrecorded. The average of two readings was taken. Age was obtained from the school records. Themean age was 10.53 (± 0.09) years and 46.9% of the recruited students were females. The mean(±SE) and median of systolic and diastolic blood pressure were 97.89 (±0.39) and 97.50 mm Hgand 57.58 (±0.39) and 60.00 mm Hg, respectively. Boys had a significantly higher systolic (99.34 ±0.56 mm Hg) and diastolic (62.59 ± 0.41 mm Hg) blood pressure than the girls (96.78 ± 0.50 mmHg systolic BP and 51.54 ± 0.55 mm Hg diastolic BP; P